Interfaith Marriage in Perspectives of Classical and Modern Scholars - Asy'ari, Asy'ari; Fisa, Triansyah (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
Interfaith marriage has been a polemic in Islam since the Quran and hadith do not clearly explain the marriage that is allowed to ahl al-kitab and how to distinguish between Ahl al-Kitab and polytheistic. Also, it differs infidel, polytheistic, Ahl al-Kitab, Majusi, Sabi’i and others. The debate over this term among scholars continues until they agree to categorize those people into Ahl al-Kitab, polytheistic, majusi and others. This research uses a qualitative method with a normative approach in which the researchers use books, journals and other scientific manuscripts as the main resources. In addition, the researchers did a survey and found several things: First, the paradigm differences of scholars regarding interfaith marriage are based on differences understanding in Quran and hadith, socio-cultural influences and methods used. Secondly, the clerics agreed to forbid a Muslim to marry a disbeliever and polytheistic, but allowed to marry women Ahl al-Kitab. Third, Scholars differ in classifying ahl al-kitab women infidel, polytheistic, ṣabi’i and Ahl al-Kitab.